PVC card cutting machine - Bariso, Lucy (Animo Repository, 2005)
Card City, Inc. employs different processes in prepaid card production. At the time this thesis was proposed, the said company was using 3x6 PVC sheets for printing these cards. Printed cards were then transferred to a separate machine, fed manually and punched out into eighteen individual cards. Although this system worked, the company wanted to use 6x8 PVC sheets to save time on printing. With this predicament, this thesis was made to enhance cutting and punching of prepaid cards using one machine to do both tasks, with process efficiency, faster production rate, and unit cost reduction without sacrificing quality. The PVC card cutting machine gave the company an edge in producing output at a faster production rate, compared to the punching machine currently used. The automated machine punched 2,496 cards an hour, against the 2,376 cards of the manual-punching machine. In comparison, between outsourcing the cutting process for the old machine and the PVC card cutting machine, the new system completed the process 6 days earlier than the old one to reach the one million targeted output. Considering the rate of printing to produce one million cards, the new system was 21 days less than the current system. With the punching process, it took 53 days to punch out one million cards using the 3x6 sheet. When the 3x8 PVC sheets of the new system were used, it took 50 days only. When both processes were combined, the company saved about 24 days in using the PVC card cutting machine. In summary, the PVC card cutting machine had 5% faster production rate and process efficiency compared to the manual punching machine.